Legal Support For The Protection Of The Rights Of Witnesses In The Fight Against Organized Crime - Giyosov Bahriddin Hasan Оgli; Kholmurodov Doniyor Bakhtiyor Оgli (The American Journal of Political Science Law and Criminology, 2020)
This article provides comments and suggestions on how to protect witnesses from law enforcement in the fight against organized crime. In addition, the foreign experience in this area and the current legislation of the Republic of Uzbekistan were analyzed.